INTEGRATION OF SUSTAINABILITY REPORT AND ESG RATING IMPLEMENTATION ON OPERATIONAL PERFORMANCE AND REPUTATION: PT PETROKIMIA GRESIK - Karmila Eka Putri; Masiyah Kholmi; Mursidi (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Research Objective: This study aims to analyze the integration of Sustainability Reports and ESG Ratings in PT Petrokimia Gresik and its impact on the company's operational performance and reputation from economic, environmental, social, and governance perspectives. Design/Methods/Approaches: A qualitative case study approach is used to explore how SR and ESG integration is implemented and internalized across the organization, with a focus on key informant insights. Research Findings : The integration of SR and ESG at PT Petrokimia Gresik significantly improves the company's operational efficiency and reputation. These elements are embedded in performance targets and decision-making, demonstrating deep organizational alignment. Theoretical/Originality contribution: This study bridges the research gap by analyzing the integration of SR and ESG simultaneously using the Triple Bottom Line framework, providing new insights into sustainability practices in Indonesia's chemical industry. Practitioner/policy implications: These findings serve as a practical guide for companies and regulators in developing sustainable business strategies and policies based on ESG data, supporting stakeholder trust and long-term competitiveness. Limitations of the study: This one-case qualitative study limits generalization and may bring subjectivity. Further quantitative or comparative research is recommended to improve external validity.